Efektifitas Clinical Nurse Educator terhadap Employee Engagment Perawat Baru Di Rumah Sakit Swasta : Literature Review - Kartika, Yuyun Nuraeni; Novita, Regina VT (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Quality nursing care services can be realized through attachment or employee engagement between  nurses orientee and the institution where they work. But in reality it is difficult to grow employee engagement, especially for  nurses orientee , this can be proven by the still high turnover of nurses in hospital institutions. This research was conducted to examine the relationship between Clinical Nurse Educator Effectiveness and employee engagement for nurses orientee. There were 20 journals used in the literature review. Journal searches were carried out through three databases, namely EBSCO, ProQuest, and Google Scholar. The results obtained are that employee engagement has a significant effect on nurse turnover intention. The things that influence employee engagement are training and career development, and the factors that influence turnover are work fatigue, work shifts, work stress, work load, work motivation and work environment. To be able to create employee engagement for nurses orientee working in an institution, it is necessary to have a Clinical Nurse Educator who has competence and has undergone continuing education.  Keywords: Empoyee Engagement, Clinical Nurse Educator, Nurse Orientee, Turn Over  ABSTRAK Pelayanan asuhan keperawatan yang berkualitas dapat diwujudkan melalui adanya keterikatan atau employee engagement antara perawat baru dengan institusi tempat bekerja. Tetapi pada kenyataannya sulit untuk menumbuhkan employee engagement khususnya terhadap perawat baru, hal ini bisa dibuktikan dengan masih tingginya turnover perawat di institusi Rumah Sakit.  Penelitian ini dilakukan untuk melihat hubungan Efektivitas Clinical Nurse Educator terhadap employee engagement bagi perawat baru. Jurnal yang digunakan dalam literature review berjumlah 20 jurnal. Penulusuran jurnal dilakukan melalui tiga database yaitu EBSCO, ProQuest, dan Google Scholar. Hasil yang didapatkan yaitu employee engagement berpengaruh signifikan terhadap turnover intention perawat, Adapun hal yang mempengaruhi employee engagement adalah pelatihan dan pengembangan karir, dan faktor yang mempengaruhi turnover adalah kelelahan kerja, shift kerja, stress kerja, beban kerja, motivasi kerja dan lingkungan kerja. Untuk dapat menciptakan employee engagement terhadap perawat baru yang bekerja di suatu institusi diperlukan adanya seorang Clinical Nurse Educator yang mempunyai kompetensi dan telah menjalani Pendidikan berkelanjutan. Kata Kunci: Empoyee Engagement, Clinical Nurse Educator, Nurse Orientee, Turn Over